Electronic Structure Calculations of A2Ti2O7 (A = Dy, Ho, and Y) - H. Y. Xiao (Advances in Condensed Matter Physics)
Ab initio calculations have been performed on titanate pyrochlores A2Ti2O7 (A = Dy, Ho, and Y) to investigate their electronic structures. The generalized gradient approximation (GGA) + U formalism has been used to correct the strong onsite Coulomb repulsion between the localized 4f electrons. The effects of effective U values on the structural and electronic properties of A2Ti2O7 (A = Dy, Ho, and Y) have been discussed. It is shown that Dy2Ti2O7 and Ho2Ti2O7 exhibit different electronic structures from Y2Ti2O7. The strong interaction between Dy and Ho 4f electrons and O 2p orbitals may increase the covalency of 〈Dy–O〉 and 〈Ho–O〉 bonds and decrease their irradiation resistance.